The outsourcing challenge: organizing workers across fragmented production networks (Brussels, 2015)
" Production networks in many sectors have become increasingly fragmented. Cutting labour costs by lowering pay, increasing work intensity and/or shifting flexibility costs to workers are just some of the motivations for outsourcing. But it can also be used to circumvent employee representation and collective bargaining systems within companies, and labour market regulations in general. Though such intentions may not drive the bulk of outsourcing decisions, any change in company boundaries is likely to impact employment, working conditions and industrial relations in the value chain.